2011
DOI: 10.1002/pon.2093
|View full text |Cite
|
Sign up to set email alerts
|

‘Open Window’: a randomized trial of the effect of new media art using a virtual window on quality of life in patients' experiencing stem cell transplantation

Abstract: An art intervention, OW, had a positive influence on health-related quality of life and patients' experiences of having a stem cell transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 34 publications
3
64
1
Order By: Relevance
“…Several studies, including some double‐blind RCTs, have been performed in this arena. SAEs were not reported in the majority of studies (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies, including some double‐blind RCTs, have been performed in this arena. SAEs were not reported in the majority of studies (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Music therapy has been shown in some studies to decrease mood disturbance and improve courageous coping, social integration, and family environment in patients undergoing HCT . An art intervention called “open window” has been shown to significantly reduce anxiety both before and after HCT …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Open Window (OW) is an innovative art intervention available at the National Stem Cell Transplant Unit at St. James's Hospital, Dublin, where patients undergo bone marrow transplantations. The study showed that the use of an art intervention in adult hospitals is possible.…”
mentioning
confidence: 99%
“…As the details of the study have already been published, 11 I will refer only to the most important results and elaborate solely on some of the difficulties encountered and their possible implications. The study showed significantly reduced levels of anxiety and depression in the group who took part in the 'Open Window' project.…”
mentioning
confidence: 99%